Prevalence and determinants of maternal healthcare utilisation among young women in sub-Saharan Africa: cross-sectional analyses of demographic and health survey data - Luchuo Engelbert Bain; Richard Gyan Aboagye; Robert Kokou Dowou; Eugene Justine Kongnyuy; Peter Memiah; Hubert Amu (BMC, 2022)
Abstract Background Maternal health constitutes high priority agenda for governments across the world. Despite efforts by various governments in sub-Saharan Africa (SSA), the sub-region still records very high maternal mortality cases. Meanwhile, adequate utilization of maternal healthcare (antenatal care [ANC], skilled birth attendance [SBA], and Postnatal care [PNC]) plays a vital role in achieving improved maternal health outcomes. We examined the prevalence and determinants of maternal healthcare utilization among young women in 28 sub-Saharan African countries using data from demographic and health surveys. Methods This was a cross-sectional study of 43,786 young women aged 15-24 years from the most recent demographic and health surveys of 28 sub-Saharan African countries. We adopted a multilevel logistic regression analysis in examining the determinats of ANC, SBA, and PNC respectively. The results are presented as adjusted Odds Ratios (aOR) for the logistic regression analysis. Statistical significance was set at p < 0.05. Results The prevalence of maternal healthcare utilisation among young women in SSA was 55.2%, 78.8%, and 40% for ANC, SBA, and PNC respectively with inter-country variations. The probability of utilising maternal healthcare increased with wealth status. Young women who were in the richest wealth quintile were, for instance, 2.03, 5.80, and 1.24 times respectively more likely to utilise ANC (95% CI = 1.80-2.29), SBA (95% CI = 4.67-7.20), and PNC (95% CI = 1.08-1.43) than young women in the poorest wealth quintile. Young women who indicated having a barrier to healthcare utilisation were, however, less likely to utilise maternal healthcare (ANC: aOR = 0.83, 95% CI = 0.78-0.88; SBA: aOR = 0.82, 95% CI = 0.75-0.88; PNC: aOR = 0.88, 95% CI = 0.83-0.94). Conclusion While SBA utilisation was high, we found ANC and PNC utilisation to be quite low among young women in SSA with inter-country variations. To accelerate progress towards the attainment of the Sustainable Development Goal (SDG) targets on reducing maternal mortality and achieving universal health coverage, our study recommends the adoption of interventions which have proven effective in some countries, by countries which recorded low maternal healthcare utilisation. The interventions include the implementation of free delivery services, training and integration of TBAs into orthodox maternal healthcare, improved accessibility of facilities, and consistent public health education. These interventions could particularly focus on young women in the lowest wealth quintile, those who experience barriers to maternal healthcare utilisation, uneducated women, and young women from rural areas.